Exploring morphological aspects, cuticle size and volatile compounds in the fruits of four olive cultivars as possibly interdependent components of Bactrocera oleae tolerance - Taiti, Cosimo; Lombardo, Luca; Godino, Gianluca; Renna, Luciana; Masi, Elisa; Marone, Elettra; Beccaluva, Marta; Ienco, Annamaria; Zelasco, Samanta; Rizzo, Santina; Perri, Enzo; Rizzo, Marianna; et al. (Frontiers in Plant Science, 2025)
Olea europaea L. subsp. europaea, var. europaea, plays a crucial role in cultural identity and economic prosperity across many regions of the Mediterranean Basin. The olive fruit fly, Bactrocera oleae, represents a major global challenge to olive and olive oil production. Its larvae feed exclusively on olive fruits, causing severe crop damage and substantial economic losses. In this study, we examined four olive cultivars differing in susceptibility to B. oleae, focusing on fruit morphology (weight, maturity index, penetration resistance), cuticle characteristics, and volatile organic compound (VOC) emissions. Confocal microscopy with Nile Red staining was used to analyze cuticle structure, while VOCs were measured using proton-transfer-reaction time-of-flight mass spectrometry (PTR-ToF-MS). Thicker cuticles were associated with reduced infestation, suggesting a mechanical barrier function against oviposition or larval penetration. PTR-ToF-MS analysis revealed cultivar- and ripening stage–specific VOC emission patterns, with certain compounds potentially acting as deterrents or attractants to the olive fly. These results indicate that fruit morphology, cuticle development, and VOC profiles act as interdependent determinants of cultivar-specific tolerance to B. oleae. The integration of these physical and chemical traits provides valuable markers for breeding programs and contributes to the development of sustainable, integrated pest management strategies in olive cultivation.